UMP undergraduates’ noble cause in Cambodia - UMP, PNC (Pejabat Naib Canselor, 2016)
A total of 20 undergraduates and four staff of University Malaysia Pahang (UMP) took part in a humanitarian mission where they carried out community service works and helped the people of Kampung Baik Anlong and Kampung Crai An Dait in Cambodia.